2012
DOI: 10.1109/tuffc.2012.2470
|View full text |Cite
|
Sign up to set email alerts
|

Direct thermal to electrical energy conversion using 9.5/65/35 PLZT ceramics in the ergodic relaxor phase

Abstract: This paper reports on direct thermal to electrical energy conversion by performing the Olsen cycle on 9.5/65/35 lead lanthanum zirconate titanate (PLZT). The Olsen cycle consists of two isothermal and two isoelectric field processes in the electric displacement versus electric field diagram. It was performed by alternatively dipping the material in hot and cold dielectric fluid baths under specified electric fields. The effects of applied electric field, sample thickness, electrode material, operating temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The energy harvesting of the PLZST thin film can be realized by using an Olsen cycle [35], as schematically guided by the red arrows in Fig. 6…”
Section: Energy Harvesting Performancementioning
confidence: 99%
“…The energy harvesting of the PLZST thin film can be realized by using an Olsen cycle [35], as schematically guided by the red arrows in Fig. 6…”
Section: Energy Harvesting Performancementioning
confidence: 99%
“…A maximum energy density of 888 J l −1 per cycle was generated at 0.0178 Hz, corresponding to a power density of 15.8 W l −1 , for operating temperatures between 25 and 160 • C and electric field cycled between 0.2 and 7.5 MV m −1 . Chin et al [54] performed a similar procedure on 9.5/65/35 PLZT ceramics and achieved a maximum power density of 55 W l −1 at 0.125 Hz. The Olsen cycle was performed between 3 and 140 • C and electric field from 0.2 to 6.0 MV m −1 .…”
Section: Dipping Experimentsmentioning
confidence: 99%
“…The Olsen cycle was performed between 3 and 140 • C and electric field from 0.2 to 6.0 MV m −1 . These studies [53,54] demonstrated that the energy conversion performance of PLZT is strongly dependent on the material composition and operating temperatures and electric fields. In fact, T Curie was reported to be −25, −10, 65, 150, 240, and 310 • C for the 65/35 Pb/Ti ratio and x = 10, 9, 8, 7, 6, and 5 mol%, respectively [55].…”
Section: Dipping Experimentsmentioning
confidence: 99%
“…The harvested thermal–electrical energy density per cycle ( W ) is equal to the area 1‐2‐3‐4 between the two P – E loops at T L and T H operated at E L and E H in Fig. , and expressed asW=EnormaldPwhere E is the electric field, and P is the polarization.…”
Section: Introductionmentioning
confidence: 99%